Dividend Policy and Corporate Value (A Meta-Analysis) - Tifani Titah Dwi Tyastari; Rosidi Rosidi; Erwin Saraswati (University of Merdeka Malang, 2017)
This study aimed to understand the effect of dividend policy on corporate value, as well as to examine and analyze the variation of result study on the corporate value in Indonesia. Dividend Signaling Model was the grand theory used to explain the effect of dividend policy on corporate value. This study used a meta-analysis approach with the sample were 70 researchers in Indonesia, both the published and unpublished in 2007-2015. The result of this study, meta-analysis strengthens the findings of the previous study which stated that the dividend policy could increase the corporate value. The differences of the previous studies were due to the presence of moderation effect from the measurement model of corporate value and dividend corporate.DOI: https://doi.org/10.26905/jkdp.v21i3.1218